Implementasi Algoritme K-Nearest Neighbour Untuk Penentuan Pada Sistem Rekomendasi Pose Menembak Senapan Angin - Mochamad Iswandaru; Dahnial Syauqy; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Shooting training so important for improve the quality of shooting accuracy, especialy for air rifle. Trainer is the important part when the athlete doing training because they can see and evaluate the training. One of indicator that trainer see when the athlete doing excercise is the movement of the rifle. Not every athlete can have trainer especialy amateur one. Stable movement of the rifle indicating that the position was right. From the problem above, need research that can replace trainer to give evaluation. To read the rifle movement in this research using HMC5883L magneto sensore with Arduino Nano using K-Nearest neighbor Algorithm. KNN methode used to find degree of angle from the rifle movement. From several test from HMC5883L sensore aquired 8,68% error percentage. From testing value of "K" aquired sucsses rate is 96%. From 10 times experiment that tested on user, system can get same value as the evaluation table was made.